Can pycnogenol prevent cisplatin-induced damage in uterus and ovaries? - Can Turkler; Tunay Kiremitli; Taylan Onat; Engin Yildirim; Gulce N. Yazici; Renad Mammadov; Mukadder Sunar (Archives of Medical Science, 2019)
Introduction Cisplatin is an antineoplastic agent, which is thought to act on tissues with increased levels of reactive oxygen species and decreased levels of antioxidants. Pycnogenol is a potent antioxidant that is used in medical conditions caused by oxidative stress. The aim of our study is to demonstrate the effects of pycnogenol on cisplatin-induced uterine and ovarian damage in rats.